2018
DOI: 10.1017/s0954422418000094
|View full text |Cite
|
Sign up to set email alerts
|

Insects as sources of iron and zinc in human nutrition

Abstract: Dietary deficiencies in Fe and Zn are globally widespread, causing serious health problems such as anaemia, poor pregnancy outcomes, increased risk of morbidity and mortality, stunted growth and impaired physical and cognitive development. Edible insects, of which a diversity of over 2000 species is available, are dietary components for about 2 billion individuals and are a valuable source of animal protein.In the present paper, we review the available information on Fe and Zn in edible insects and their poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 68 publications
(97 reference statements)
3
86
1
12
Order By: Relevance
“…Cu, Mn, and Fe contents of T. molitor larvae grown on non-spiked wheat bran were close to values reported for mealworm larvae in other feeding trials 19,50 , underlining the micronutrient quality of the applied bran material. Yet, the metals were differently impacted by Zn-biofortification.…”
Section: Discussionsupporting
confidence: 81%
“…Cu, Mn, and Fe contents of T. molitor larvae grown on non-spiked wheat bran were close to values reported for mealworm larvae in other feeding trials 19,50 , underlining the micronutrient quality of the applied bran material. Yet, the metals were differently impacted by Zn-biofortification.…”
Section: Discussionsupporting
confidence: 81%
“…Mwangi et al. () suggested that locusts are alternative protein sources containing iron and zinc at a higher level than in animal‐based food sources for improving human nutrition. The contents of other microminerals (copper and manganese) in locust powder were extremely high and more than 100% of the RDA or AI similar to those in crickets (Montowska et al., ), whereas contents of sodium and potassium were insufficient for the value of RDA or AI.…”
Section: Resultsmentioning
confidence: 99%
“…This is often to combat iron deficiency anaemia which affects more than a quarter of the children (Lopez et al, 2016). Many insect species have shown not only to have a high concentration of iron but also of zinc (Mwangi et al, 2018).…”
Section: Humansmentioning
confidence: 99%